Anhidrosis - Ahmad, Bashir; Goriman Khan, Mohd Azam Khan; Abdullah, Rasedee (Veterinary Association Malaysia, 2006)
Anhidrosis with emphasis on etiopathogenesis is reviewed in this paper. Anhidrosis, a non-sweating syndrome in horses, first reported in 1925, was mainly observed in temperate horses introduced into the hot humid environment. This phenomenon is believed to be a compensatory mechanism for profuse sweating. Anhidrosis can cause reduced performance; elevated respiratory rate, discomfort, varying degree of anorexia and alopecia. Death may ensue as a result of a heat stroke. Feeding, hypothyroidism, hereditary factors, exhaustion of adrenaline, electrolyte imbalance and atrophy of sweat gland may contribute to anhidrosis. The condition can easily be diagnosed from clinical signs. There is no specific treatment, but transferring the horse to a cooler climate or stabling under air-conditioning, in conjunction with vitamin E or ethy lenediamine dihydrioidide, may improve the condition.